Differential viral kinetics in treated genotype 4 chronic hepatitis C patients according to ethnicity. - Elefsiniotis, I S; Pavlidis, C; Dimitroulopoulos, D; Vezali, E; C Mihas; Mariolis-Sapsakos, T; Koutsounas, S; Paraskevas, E; Saroglou, G (J Viral Hepat, 2009)
Data concerning the efficacy of PEG-IFN alpha 2a plus ribavirin treatment in treatment-naive, genotype 4-infected chronic hepatitis C (CHC) patients from Europe are limited. Hence the aim of this study was to investigate the viral kinetics as well as the sustained virological response (SVR) rates and their predictors, in these patients. One hundred and twenty-three patients were retrospectively analysed. Early (EVR) and late virological response (LVR) was confirmed by undetectable (<50 IU/mL) serum HCV-RNA at week 12 and week 24 of treatment, respectively. SVR was confirmed by undetectable serum HCV-RNA at the end of treatment as well as 6 months later. Overall, 43.5% of patients exhibited SVR, 42.6% were nonresponders and 13.9% were relapsers. EVR was observed in 40.74% and LVR in 59.25% of them. The positive predictive values of EVR and LVR were 72.97% and 86.27% whereas their negative predictive values were 64.29% and 92.85%, respectively. EVR independently predicted SVR in Caucasian patients (P < 0.001) but not in Egyptian patients (P = 0.613), in whom the only independent predictor of SVR was the absence of cirrhosis (P = 0.004). LVR seems to be a better predictor of SVR than EVR in the vast majority of genotype 4-infected CHC patients, irrespective of ethnicity and all the other baseline parameters.
Keywords: Adult; Antiviral Agents; Ethnic Groups; Europe; Female; Genotype; Hepacivirus; Hepatitis C, Chronic; Humans; Interferon alpha-2; Interferon-alpha; Male; Middle Aged; Polyethylene Glycols; Predictive Value of Tests; Recombinant Proteins; Ribavirin; RNA, Viral; Treatment Outcome; Viral Load